Changes in the tourist function of Kujawy health resorts (based on the capacity and type of accommodation) - Matczak, Andrzej (Turyzm/Tourism, 2019)
The article is an attempt to verify the hypothesis that the tourist function in Polish health resorts is becoming increasingly diversified. It presents data concerning the capacity and type of accommodation in three Kujawy health resorts, as well as their amenities. The data was provided by the Local Data Bank at the Central Statistical Office (GUS), and refers to the period between 1995 and 2018. The study findings point to the increasingly diversification of the tourist function in Kujawy health resorts. The greatest changes have been identified at Ciechocinek which can currently be defined as a tourism and health resort. Less advanced changes have been found in Inowrocław, while Wieniec-Zdrój still remains a typical spa with a marginal share of other functions. Based on official statistics, the author has identified general trends taking place in health resort infrastructure. Only a limited quantitative analysis of the relationship between the health and tourist functions of Kujawy health resorts has been made, mostly due to the incompleteness of the statistical data.